Prevalence of Cervical Stenosis and Myelopathy in Patients With Idiopathic Normal Pressure Hydrocephalus. (1st September 2019) - Naylor, Ryan M; Lenartowicz, Karina; Graff-Radford, Jonathan; Cutsforth-Gregory, Jeremy; Elder, Benjamin D
Abstract: INTRODUCTION: Both idiopathic normal pressure hydrocephalus (iNPH) and cervical myelopathy may result in progressive gait impairment. It is possible that some of the patients who do not respond to shunting despite a positive tap test may have gait dysfunction from cervical myelopathy. The objective of this study was to determine the prevalence of cervical stenosis with or without myelopathy in patients with iNPH. METHODS: We screened a consecutive series of patients who underwent shunt placement for iNPH for comorbid cervical stenosis. Clinical manifestations of iNPH and cervical myelopathy, grade of cervical stenosis based on previously published criteria, cervical spine surgical intervention, timing of intervention, and outcomes were recorded. RESULTS: A total of 42 patients with iNPH were included for analysis. Slightly more patients were male (65%), with a mean age of 75 yr (SD 7 yr) for the entire cohort. All patients presented with gait disturbances and underwent cervical spine MRI. 30/42 (71%) had at least cervical stenosis, while 7/42 (17%) had significant (grade 2-3) cervical stenosis with myelopathy requiring surgical decompression. All patients with grade 2-3 cervical stenosis and symptoms of cervical myelopathy in addition to iNPH underwent cervical decompression surgery. CONCLUSION: Clinically significant cervical stenosis is highly prevalent in patients with iNPH, though this finding requires validation in a larger population. Based on these results, cervical imaging should be considered preoperatively or in patients whose gait does not improve after shunt placement.